Antihyperglycemic Effect of Different Fractions of Methanol Extract of Ceiba pentandra Leaves - Kharat, A.R.; Das, S.; Kharat, K.R. (Pharmaceutical Research - Recent Advances and Trends Vol. 4, 2024)
The present study investigated the antihyperglycemic effect of different fractions of methanol extract of Ceiba pentandra leaves. Chronic hyperglycemia during diabetes causes glycation of body proteins that in turn leads to secondary complications affecting e, kidneys, nerves and arteries. Petroleum ether, chloroform, ethyl acetate and methanol fractions of Ceiba pentandra leaves were prepared and administered individually at different doses to different batches of rats (both normal and alloxan diabetic rats) after an overnight fast. The blood glucose levels were measured at 0, 2, 4 h, 7 and 14 days after the treatment. The antihyperglycemic activity of Ceiba pentandra leaves was compared with the treatment of glibenclamide, an oral hypoglycemic agent. The results indicate that C. pentandra possesses significant antihyperglycemic activity. All fractions except petroleum ether fraction even if with a different degree, have shown significant reduction in blood glucose levels in alloxan-induced diabetic rats. The methanol fraction has shown maximum effect in all the two tests compared to the other extracts. The methanol fraction of Ceiba pentandra at a dosage of 200 mg/kg body weight shows a maximal blood glucose lowering effect in diabetic rats.